Forceful or persistent: How the ECB's new inflation target affects households' inflation expectations - Mathias Hoffmann; Emanuel Mönch; Lora Pavlova; Guido Schultefrankenfeld (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
We study how households adjust their medium-term inflation expectations under the new ECB inflation targeting strategy. Survey respondents make little difference between the previous strategy of targeting inflation rates close to but below 2% and the new strategy with a 2% point target. Participants who learn about the inherent asymmetry in the ECB's reaction to potential off-target inflation expect moderately higher medium-term inflation. Respondents asked to assume a scenario of current inflation running below target place a significantly higher probability on medium-term outcomes above 2%. In a scenario of inflation currently running above target, however, participants do not in turn expect an undershooting of medium-term inflation.
Keywords: F33; E31; E52; 330; Monetary Policy Strategy; Household Inflation Expectations; Randomized Control Trial; Survey Data